Case reportTinea cutis glabrae: causes of diagnostic challenge - Jakubowicz, Oliwia; Łuczkowska, Magdalena; Żaba, Ryszard; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Dermatophytoses belong to the most common disease entities encountered in everyday dermatological practice. Despite the fact that their clinical presentation, course and treatment response remain rather typical, they often present a considerable diagnostic and therapeutic challenge. We present a case of a 54-year-old male who presented to the outpatient clinic of the Department of Dermatology in December 2012 with the diagnosis of erythema gyratum repens for further diagnosis and treatment of skin lesions gradually intensifying in the previous 2 years. The skin changes presented as spreading annular erythematous lesions, with papules and plaques located peripherally, and accompanying pruritus. Due to the clinical presentation and anamnesis, working conditions (poultry farm), and lack of response to previous treatment, mycological culture was performed. Epithelial scrapings of the trunk and the groins proved to be positive. After 3 weeks, Trichophyton mentagrophytes var mentagrophytes was identified by epithelial cell culture.